GROWTH AND FERMENTATION CHARACTERISTICS OF NEW SELECTED STRAINS OF SACCHAROMYCES AT HIGH-TEMPERATURES AND HIGH CELL DENSITIES - Laluce, Cecília [UNESP]; Palmieri, M. C.; Dacruz, RCL (Wiley-Blackwell, 1991)
Maintenance of high cell viability was the main characteristic of our new strains of thermotolerant Saccharomyces. Total sugar conversion to ethanol was observed for sugarcane juice fermentation at 38-40-degrees-C in less than 10 h and without continuous aeration of the culture. Invertase activity differed among the selected strains and increased during fermentation but was not dependent on cell viability. Invertase activity of the cells and optimum temperature for growth, as well as velocity of ethanol formation, were dependent on medium composition and the type of strain used. At high sugarcane syrup concentrations, the best temperature for ethanol formation by strain 781 was 35-degrees-C. Distinct differences among the velocities of ethanol production using selected strains were also observed in sugarcane syrup at 35-38-degrees-C.
Keywords: YEAST THERMOTOLERANCE; SACCHAROMYCES; INVERTASE; SUGARCANE JUICE FERMENTATION